Tusok tusok discussing and visualizing the intersection of Filipino food and class issues through an independent publication - Shivers, Ysabelle Therese S.
This study aims to examine the phenomenon of Filipino street food being repackaged and recontextualised into more refined and formal eating spaces (such as restaurants and hotels), and what effects this has on the meaning or social role of the food itself, if any. I employed to tiers of data gathering, the first being a structured visual analysis of street food dishes and their environmental context, limited to establishments in the Diliman area. The second involved me asking questions and having conversations with vendors, street food regulars, and key informants involved in the food industry. Through the data and insight gathered, I was able to make the following assertions. Social context, i.e., street food culture's intimate relationship with the diner and it being a natural reaction to the demand for accessible, affordable, and filling food, is something that cannot be divorced from the object (the food) itself. The street food itself as an object, and the "experience" of street food are anchored to this -- therefore one cannot simply make something appear as street food or make it more sophisticated out of its original context without it losing this social meaning. Additionally, I was able to deduct, from my conversations with vendors and diners, that there is a need to fortify the industry and the culture to ensure its endurance. My research further argues that this act of appropriation is not because the elite are becoming more sympathetic and willing to engage in "lower" culture or cuisine -- instead, through their enjoyment of the aesthetics of street food, it merely becomes novelty. Repackaging street food for a venue completely removed from its social context, this research finds, is unconcerned with addressing issues of the threat of commercialization and inflation on the vendors, the already mostly unregulated street food industry, and consequently, the working class Filipino. Any push to properly regulate this industry by the government must address these issues, and offer more security and stability to the livelihood of the vendors; it must not be for the sole purpose of impressing tourists. En masse, my research hopes to be able to echo a larger issue at hand by examining a microcosm that is the appropriation of street food: the ongoing efforts to sanitize or even erase the cultures and livelihoods of the underprivileged through aggressive gentrification, all in the name of entertaining more middle-class (and above, of course) tastes, sensibilities, and lifestyle. In response to these issues, I have conceptualized Tusok Tusok: an independent, non-commercial publication that discusses the intersections between Filipino food, class, and space. It acts as a gateway to Filipino food literature and as a preface to the various issues concerning food systems and consumption. The main interest of this publication is to get those in the target audience who are not informed or previously invested in these relevant issues (i.e., commercialization, privatization of public spaces, class appropriation, etc.) interested in thinking of their food beyond simply an object of consumption or indulgence. Rather, the publication (and the entire campaign, to an extent) will act in aid of presenting food as a material and cultural deposit, making it a fertile subject for further academic and cultural studies, especially through the lens of Filipino cuisine and dining traditions. Additionally, beyond simply thinking about food in these more thorough ways, long-term behavioral change is encouraged (and is ultimately the most aspirational goal in mind for the publication) -- entailing that the audience puts this knowledge into practical action by being more discerning and critical of their regular food consumption.